2006
DOI: 10.1007/s10661-006-9253-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects of dredging on sediment nutrients, carbon and granulometry in a tropical estuary

Abstract: This monitoring study encompassed a period prior to dredging, during dredging and post dredging between July 1999 to June 2000 in Ponggol estuary located along the northeastern coast of Singapore. Mean concentrations of sediment nutrients in mg x Kg(-1) (+/- standard error of means) prior to dredging, during dredging and post dredging were 9.75 +/- 4.24, 8.18 +/- 4.29 and 11.46 +/- 4.74 for ammonium, 0.08 +/- 0.05, 0.06 +/- 0.02 and 0.09 +/- 0.01 for nitrite, 0.04 +/- 0.04, 0.11 +/- 0.17 and 0.25 +/- 0.30 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 36 publications
3
24
0
2
Order By: Relevance
“…The toxicity of nitrite may be due to the reaction of nitrite with sec ondary amines to produce the carcinogenic nitrosamine [29]. These results agree with that recorded by other invistigators [30] including Mohammed et al, who re corded a high level of nitrite (0.30 -0.32 mg /L) in water of Qarun Lake [31].…”
Section: Discussionsupporting
confidence: 80%
“…The toxicity of nitrite may be due to the reaction of nitrite with sec ondary amines to produce the carcinogenic nitrosamine [29]. These results agree with that recorded by other invistigators [30] including Mohammed et al, who re corded a high level of nitrite (0.30 -0.32 mg /L) in water of Qarun Lake [31].…”
Section: Discussionsupporting
confidence: 80%
“…Concomitantly, a small fraction of organic carbon was oxidized and ammonia was released (Table 1). A study on the environmental effects of dredging activities in the Pongol estuary, Singapore (Nayar et al 2007) also showed elevated levels of ammonia and depletion of organic carbon during and after sediment removal. The effects of homogenization on metal concentrations observed in this study were in accordance with earlier findings (van den Berg et al 2000).…”
Section: Effects Of Sediment Homogenization and Redepositionmentioning
confidence: 98%
“…5). Elevated levels of organic matter associated with dredged sediments and deposition of finegrained sediment in dredge pits have been documented by researchers elsewhere (Johnnston 1981, Nayar et al 2007, Palmer et al, 2008. In very deep dredge pits such as located in Lake Pontchartrain's, sulfate reduction was dominant process of organic matter degradation (Flocks&Franze 2002).…”
Section: An Extent Of Deep Dredging Impactmentioning
confidence: 97%